KEPUASAN KERJA DITINJAU DARI KOMUNIKASI INTERPERSONAL DAN BUDAYA ORGANISASI - Flora Grace Putrianti (JURNAL SPIRITS, 2013)
ABSTRACT This research were aimed to find out the relationship between the interpersonal communication and organizational culture with the job satisfaction, the relationship between the interpersonal communication with the job satisfaction and the relationship between organizational culture with the job satisfaction of lecturer at Universitas Sarjanawita Tamansiswa Yogyakarta.The data were collected by using job satisfaction scales, interpersonal communication scales and organizational culture scales. The research was conducted at the Universitas Sarjanawita Tamansiswa Yogyakarta. The total number of the subjects were 58 that meet the criteria as a research subject.Data were analyzed by using multiple regression analysis and partial correlation analysis, by using SPSS version 17.0 statistical program as a tool. Theresult regression analysis showed : a) There were correlation between the interpersonal communication and the organizational culture with the job satisfaction. The result showed R=0,638 and Adjusted R Square (R²)=0,406, b) there were correlation positively between the interpersonal communication with job satisfaction. The result showed R partial=0,544 (p=0,000) and effective contribution=29,6% and c) there were correlation positively between organizational culture with job satisfaction. The result showed R partial=0,505 (p=0,000)  and effective contribution=25,5%.Key words : Job Satisfaction, Interpersonal Communication, Organizational